2014
DOI: 10.1007/s10557-014-6520-2
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3: A Modifiable Risk Factor in Heart Failure

Abstract: Myocardial galectin-3 is upregulated upon cardiac stressors such as angiotensin II and pressure overload leading to cardiac remodeling and heart failure. The expression level of galectin-3 mirrors the progression and severity of heart failure and therefore, galectin-3 is being used as a biomarker for heart failure. However, as galectin-3 is causally involved in pathological myocardial fibrosis it has been suggested that galectin-3 also actively contributes to heart failure development. In this review we discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 47 publications
2
57
0
6
Order By: Relevance
“…Galectin-3 was an independent predictor for LVEF after 4 months. Elevated levels were correlated with a significant lower LVEF (van der Velde et al, 2014). Further clinical data are scarce and suggest a potential relationship between galectin-3 levels and higher risk of HF development after MI.…”
Section: Clinical Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…Galectin-3 was an independent predictor for LVEF after 4 months. Elevated levels were correlated with a significant lower LVEF (van der Velde et al, 2014). Further clinical data are scarce and suggest a potential relationship between galectin-3 levels and higher risk of HF development after MI.…”
Section: Clinical Studiesmentioning
confidence: 88%
“…Clinically, MRAs improve survival in patients with symptomatic chronic HF after MI (Maisel et al, 2014;Pitt et al, 2003). Recently, it was shown that MRAs reverse cardiac and renal expression of galectin-3 in hypertensive rats (Calvier et al, 2015).…”
Section: Effects Of Mras On Galectin-3-induced Fibrosismentioning
confidence: 99%
“…Despite its role as a biomarker that mirrors the progression and severity of heart failure, 53 galectin-3 does not play a crucial role in the pathogenesis of the fibrotic cardiomyopathy associated with pressure overload. Useful and reliable biomarkers of cardiac remodeling do not necessarily serve a key biological function, but they may be released after stress, reflecting another injurious process.…”
Section: Discussionmentioning
confidence: 99%
“…Однако, кроме напряжения стенки миокарда, в патогенезе ХСН также принимают участие и другие про-цессы, такие как воспаление и фиброз. Натрийуретические пептиды не дают возможности оценивать выраженность данных процессов, в связи с чем поиск биомаркеров фиброза и воспаления является актуальным.В исследованиях DEAL-HF и СOACH была продемон-стрирована способность нового биомаркера галектина-3 отражать процессы воспаления и фиброза, лежащих в осно-ве ремоделирования миокарда у пациентов с ХСН [1][2][3].Галектин-3 принадлежит к семейству β-галактозид-связывающих протеинов. Благодаря наличию в своей Гямджян К. А., Кукес В. Г. p=0.02).…”
unclassified
“…В исследованиях DEAL-HF и СOACH была продемон-стрирована способность нового биомаркера галектина-3 отражать процессы воспаления и фиброза, лежащих в осно-ве ремоделирования миокарда у пациентов с ХСН [1][2][3].…”
unclassified